Oleic acid enhances the production of reactive oxygen species in neuronal tissue - J. L. Alves; A. S. C. Figueira; M. Souto; I. L. Lopes; J. C. Dionísio; R. M. Quinta-Ferreira; M. E. Quinta-Ferreira (Energy Reports, 2020)
One of the major current goals is to obtain clean energy sources and to replace petroleum-derived fuel by biodiesel, which is made from biodegradable and renewable biomass such as vegetable oils. In particular, olive oil contains large amounts of oleic acid (OA), which is a monounsaturated fatty acid used for energy production and also for biosensors, nutritional products, pharmaceuticals and cosmetics. Since oleic acid is particularly abundant in olive oil, large concentrations of this fatty acid may exist in the effluents of olive mill production units, which need to be treated in order to avoid water contaminations and undesirable effects in the ecosystem. Indeed, this type of organic waste, which is potentially useful in the production of biodiesel, in excess may be toxic and cause neurodegeneration, through the production of cellular reactive oxygen species (ROS). The effect of 10-100~μM of oleic acid on neuronal ROS production was evaluated in brain slices incubated with the permeant fluorescent ROS indicator H2DCFDA. The experiments revealed that the amplitude of the ROS signals, corrected for the autofluorescence, increased slightly for the OA concentrations in the range 60-100~μM.
Keywords: 330; Biomass; Autofluorescence; HDCFDA indicator; Hippocampal CA3 area; Oleic acid; ROS